Classification of the cutaneous manifestations of COVID‐19: a rapid prospective nationwide consensus study in Spain with 375 cases. (10th June 2020) - Galván Casas, C.; Català, A.; Carretero Hernández, G.; Rodríguez‐Jiménez, P.; Fernández‐Nieto, D.; Rodríguez‐Villa Lario, A.; Navarro Fernández, I.; Ruiz‐Villaverde, R.; Falkenhain‐López, D.; Llamas Velasco, M.; García‐Gavín, J.; Baniandrés, O.; et al.
Summary: Background: The cutaneous manifestations of COVID‐19 disease are poorly characterized. Objectives: To describe the cutaneous manifestations of COVID‐19 disease and to relate them to other clinical findings. Methods: We carried out a nationwide case collection survey of images and clinical data. Using a consensus we described five clinical patterns. We later described the association of these patterns with patient demographics, the timing in relation to symptoms of the disease, the severity and the prognosis. Results: The lesions may be classified as acral areas of erythema with vesicles or pustules (pseudo‐chilblain) (19%), other vesicular eruptions (9%), urticarial lesions (19%), maculopapular eruptions (47%) and livedo or necrosis (6%). Vesicular eruptions appear early in the course of the disease (15% before other symptoms). The pseudo‐chilblain pattern frequently appears late in the evolution of the COVID‐19 disease (59% after other symptoms), while the rest tend to appear with other symptoms of COVID‐19. The severity of COVID‐19 shows a gradient from less severe disease in acral lesions to more severe in the latter groups. The results are similar for confirmed and suspected cases, in terms of both clinical and epidemiological findings. Alternative diagnoses are discussed but seem unlikely for the most specific patterns (pseudo‐chilblain and vesicular). Conclusions: We provide a description of the cutaneous manifestations associated with COVID‐19 infection. These may help clinicians approach patients with the disease and recognize cases presenting with few symptoms. What is already known about this topic? Previous descriptions of cutaneous manifestations of COVID‐19 were case reports and mostly lacked illustrations. What does this study add? We describe a large, representative sample of patients with unexplained skin manifestations and a diagnosis of COVID‐19, using a consensus method to define morphological patterns associated with COVID‐19. We describe five clinical patterns associated with different patient demographics, timing and prognosis, and provide illustrations of these patterns to allow for easy recognition. Linked Editorial:  Hay et al . Br J Dermatol 2020; 183 :3–4 . Abstract : Linked Editorial:  Hay et al . Br J Dermatol 2020; 183 :3–4 . Plain language summary available online